Panel Discussion 1 | Investing in open infrastructure and service: The benefits and challenges - BARBOUR, Ginny (Institutional Knowledge at Singapore Management University, 2021)
Covered the problem, benefits, challenges and opportunities in open infrastructure. Discussed fostering bibliodiversity, how open infrastructure supported good science, the impact of the UNESCO Recommendation on Open Science.